A REVIEW OF HIGH-SPEED RAIL PLAN IN JAVA ISLAND: A COMPARISON WITH EXISTING MODES OF TRANSPORT - Eko Hartono; Imam Muthohar (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2013)
In order to provide better transportation systems, Indonesian Government is planning to develop a new high-speed rail system in Java that will connect two biggest cities in Java Island, Jakarta and Surabaya, with approximately 685 kilometers of entirely new track. This paper reviewed the Indonesian Government’s plan to develop the high-speed rail in term of comparison to existing modes of transport.This study employs demands projection of high-speed rail using JETRO method and benchmarking from other countries’ high speed rails. Furthermore, air pollution caused by transport mode was calculated based on the emission factor from CACP & CNT. The last is generalized cost that considers total time to travel as value of money.It can be concluded that journey time and fare of the high-speed rail is very competitive to the air transport in Jakarta-Surabaya corridor. The journey time to travel from Jakarta to Surabaya is 4 hours and 19 minutes by high-speed train and 4 hours and 40 minutes by air. Based on the benchmarking analysis, the suitable fare for the high-speed rail should be 70% of the air transport. This study predicted that 61% of air passenger, 18% of conventional rail passenger and 12% of bus passenger will switch to the high-speed rail service in 2020. In total, the high-speed rail will have 24% of market share for the passenger transport and becomes the second largest market share after road transport (52%). The conventional rail and air transport have 14% and 9% of total market share to travel from Jakarta to Surabaya and vice versa. The high-speed rail development reduces carbon emissions caused by transportation systems in Java Island. It has been calculated that there are 2.542 million tonnages of CO2 per annum without introducing high-speed rail, however, the CO2 emissions decrease to 1.694 million tonnages per annum if the high-speed rail is developed in Java Island. Generalized cost of the high-speed rail is higher than road and conventional rail. However, it is lower than air transport.Keywords: Java high-speed rail, HSR Comparison, modal share, journey time